Prebiotic effects of white button mushroom (Agaricus bisporus) feeding on succinate and intestinal gluconeogenesis in C57BL/6 mice - Yuan Tian (Journal of Functional Foods, 2018)
The mechanisms by which white button (WB) mushrooms (Agaricus bisporus) may influence health are unclear. WB feeding (1%) resulted in changes in the composition of microbiota in conventional (CV) mice to expand a population of Prevotella that produce propionate and succinate. Microbial propionate and succinate production induced expression of genes important for intestinal gluconeogenesis (IGN) via the gut-brain neural circuit. Reduced hepatic glucose production was a metabolic benefit of IGN that was found in WB fed CV mice. In the absence of microbiota or in mice with disruptions in the ability to sense microbiota there was no WB mediated effect. WB-fed lean mice had a small but significant improvement in glucose sensitivity. WB feeding resulted in shifts in the microbiota that induced IGN and improved glucose homeostasis.